TEACHING SPOKEN ENGLISH TO UPPER CLASS PUPILS (Conference Zone, 2022)
Speaking is defined as an effective means for those students who learn a foreign language as a second for end of communication with other individuals or on the other hand speaking is a way of successfulness for learner of foreign language so as to make an easy communication with others.